2021
DOI: 10.1111/febs.15718
|View full text |Cite
|
Sign up to set email alerts
|

The ups and downs of growth hormone secretagogue receptor signaling

Abstract: The growth hormone secretagogue receptor (GHSR) has emerged as one of the most fascinating molecules from the perspective of neuroendocrine control. GHSR is mainly expressed in the pituitary and the brain, and plays key roles regulating not only growth hormone secretion but also food intake, adiposity, body weight, glucose homeostasis and other complex functions. Quite atypically, GHSR signaling displays a basal constitutive activity that can be up-or downregulated by two digestive system-derived hormones: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 153 publications
(293 reference statements)
0
30
0
1
Order By: Relevance
“…Interestingly, LEAP2 and ghrelin display similar binding affinities for GHSR ( Ge et al, 2018 ; M'Kadmi et al, 2019 ; Wang et al, 2019 ), but plasma LEAP2 levels are ∼10-fold higher than plasma ghrelin levels in satiated rodents and humans ( Mani et al, 2019 ; Fittipaldi et al, 2020 ). Thus, modulatory actions of LEAP2 on GHSR, such as those revealed here, may play a more dramatic role than ghrelin itself in some physiological GHSR functions ( Cornejo et al, 2021 ). On the other hand, plasma ghrelin mainly acts on brain targets near the fenestrated capillaries, such the hypothalamic arcuate nucleus or the area postrema ( Schaeffer et al, 2013 ; Cabral et al, 2014 ; Cabral et al, 2017 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Interestingly, LEAP2 and ghrelin display similar binding affinities for GHSR ( Ge et al, 2018 ; M'Kadmi et al, 2019 ; Wang et al, 2019 ), but plasma LEAP2 levels are ∼10-fold higher than plasma ghrelin levels in satiated rodents and humans ( Mani et al, 2019 ; Fittipaldi et al, 2020 ). Thus, modulatory actions of LEAP2 on GHSR, such as those revealed here, may play a more dramatic role than ghrelin itself in some physiological GHSR functions ( Cornejo et al, 2021 ). On the other hand, plasma ghrelin mainly acts on brain targets near the fenestrated capillaries, such the hypothalamic arcuate nucleus or the area postrema ( Schaeffer et al, 2013 ; Cabral et al, 2014 ; Cabral et al, 2017 ).…”
Section: Discussionmentioning
confidence: 84%
“…The bioactive portion of LEAP2 resides at the N-terminal region of the peptide, which binds to GHSR and impairs both ghrelin-evoked and constitutive signaling pathways ( M'Kadmi et al, 2019 ). Thus, GHSR activity is regulated by at least two endogenous ligands, ghrelin and LEAP2, that display opposite actions ( Cornejo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Setting aside the findings in the latter four studies, the aforementioned data led to the hypothesis that LEAP2 might offset the actions of acyl-ghrelin and contribute to the state of ghrelin resistance associated with obesity [ [20] , [21] , [22] , [23] ]. For example, acyl-ghrelin fails to acutely induce food intake in diet-induced obese mice and in obese Agouti mice whether acutely or chronically administered [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin is a peptide hormone that operates through the binding and activation of the G protein-coupled receptor (GPCR) named growth hormone secretagogue receptor (GHSR). GHSR regulates various key physiological processes in particular the ones related to energy homeostasis including glucose metabolism [1,2]. Indeed, ghrelin administration induces blood glucose elevation and reduction in circulating insulin in humans and rodents [3].…”
mentioning
confidence: 99%
“…We previously reported that LEAP2 displays Ki value within the nanomolar range (1.26 AE 0.05 nM) and a pA 2 value of 7.99 AE 0.15 with respect to Gq-induced intracellular calcium mobilization [6]. Since then, a great deal of studies devoted to delineating LEAP2 function indicated that this peptide counteracts ghrelin-mediated actions including food intake and growth hormone secretion in rodent models [2,5,6,8]. Despite this rapid progress in characterizing LEAP2 activity, the effect of this peptide on glucose-stimulated insulin secretion is unknown.…”
mentioning
confidence: 99%